Chemo-enzymatic access to C-4′-hydroxyl-tetrahydrofurano-spironucleosides. (11th January 2021) - Rungta, Pallavi; Kumar, Manish; Mangla, Priyanka; Kumar, Sandeep; Prasad, Ashok K.
Abstract : The biocatalytic synthesis of C -4′-hydroxyl-tetrahydrofurano-spironucleosides where the tetrahydrofuranospirocyclic ring at C -4′ position locks the furanose ring of nucleosides in the NE-conformation (C4′- exo ). Abstract : The demand to attain structural pre-organisation and recognition in potential antiviral agents has provoked spirocyclic restriction to be incorporated in nucleosides. With an aim to achieve pre-organization, C -4′-hydroxyl-tetrahydrofurano-spironucleosides have been synthesised from the naïve d -glucose via an intramolecular cyclisation route starting in over 10 steps. The process involves the Lipozyme® TL IM-mediated monoacetylation of the primary hydroxyl group of 4- C -hydroxymethyl-1, 2, 5, 6-di- O -isopropylidene-β-l -mannofuranose. The assessment for the selectivity of monoacylation in the dihydroxymannofuranose sugar derivative using various vinyl esters revealed that different acyl chain lengths did not affect the selectivity of lipase but led to an increase in the rate of reaction with increasing chain length. A hydroxytetrahydrofuran ring, which is a C -4′-spirocycle on furano-nucleoside, was picked as the modification to furnish C4′- exo, NE-conformational restriction in the nucleosides, which conclusively revealed that the bicyclic framework did not bind the sugar pucker to the anticipated N/S-conformation only.